Growth Response and Crop Production (Brassica Juncea L.) Against Watering Time Interval at Various Hydroponics Media - Muhammad Zailani; Retno Astuti Kuswardani; Ellen L. Panggabean (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
This study aims to determine the Response Growth and Production of Crops (Brassica juncea L.) Against Watering Time Interval In Various Hydroponics Media. The research was conducted at the experimental gardens of Faculty of Agriculture, Faculty of Agriculture, University of Medan Area, located on No. Pond Street. 1 Medan Estate. This research was conducted from October 2013 until December 2013. The design used was RAL Factorial, with 2 replications, 10 combinations. The first factor of the hydroponic planting medium is: M1: Frying Roots, M2: Coconut Coir Powder, M3: Fryer Seal, M4: Rokwool, and M5: Sawdust, the second factor is the time interval: I1: 3 hours a day I2: 5 hours a day, starting from 08:00 a.m to 06:00 p.m. The result of this research indicates that the treatment of watering liquid fertilizer with different time interval does not show a real effect on the growth of mustard plants, Media treatment used on hydroponic systems have an influence very evident on the parameters of plant height, leaf number, leaf area, production weight and significant effect on leaf level parameters, influential planting medium and have the best number is M3 (fuel husk). Interaction interval of watering time on various hydroponic media did not have a significant effect on observed parameters, namely: plant height, leaf number, wet weight, and weight of production, while the leaf color parameter had significant effect on leaf width.